2005
DOI: 10.7150/ijbs.1.67
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Personalities of the Regulatory Subunit of Protein Kinase CK2: CK2 Dependent and CK2 Independent Roles Reveal a Secret Identity for CK2β

Abstract: Protein kinase CK2 (formerly casein kinase II), an enzyme that participates in a wide variety of cellular processes, has traditionally been classified as a stable tetrameric complex consisting of two catalytic CK2α or CK2α' subunits and two regulatory CK2β subunits. While consideration of CK2 as a tetrameric complex remains relevant, significant evidence has emerged to challenge the view that its individual subunits exist exclusively within these complexes. This review will summarize biochemical and genetic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
165
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 119 publications
(225 reference statements)
11
165
0
2
Order By: Relevance
“…Moreover, live-cell fluorescent imaging and X-ray crystallography studies (Niefind et al, 2001) have revealed the subcellular dynamics of CK2 subunits and the transient nature of their interaction. These data again support of the notion that at least some aspects of CK2b functions are not based on its interaction with the CK2 catalytic subunit (Filhol et al, 2004;Bibby and Litchfield, 2005). In mice as well as in Caenorhabditis elegans, a functional loss of CK2b is lethal, demonstrating that the protein is essential for viability (Fraser et al, 2000;Buchou et al, 2003).…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Moreover, live-cell fluorescent imaging and X-ray crystallography studies (Niefind et al, 2001) have revealed the subcellular dynamics of CK2 subunits and the transient nature of their interaction. These data again support of the notion that at least some aspects of CK2b functions are not based on its interaction with the CK2 catalytic subunit (Filhol et al, 2004;Bibby and Litchfield, 2005). In mice as well as in Caenorhabditis elegans, a functional loss of CK2b is lethal, demonstrating that the protein is essential for viability (Fraser et al, 2000;Buchou et al, 2003).…”
Section: Introductionsupporting
confidence: 73%
“…Binding of P1 to CK2b may compete for a common binding site on the protein for unknown endogenous ligands that are essential for cell survival. There is mounting evidence that the two CK2 subunits can exist in their free form outside the tetrameric complex (Bibby and Litchfield, 2005;Filhol et al, 2004). For instance, more than 40 different proteins were shown to interact with CK2b, and importantly, this protein was characterized as a regulatory binding partner of several protein kinases involved in cell signalling (Guerra and Issinger, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CK2 appears distributed in tetrameric complexes inside the cells but significant evidence indicates that the individual subunits do not exist exclusively within these complexes but also as free proteins (Litchfield, 2003;Bibby and Litchfield, 2005).…”
Section: Introductionmentioning
confidence: 99%